Performance Evaluation of a TP-Link CPE220 Point-to-Point Wireless Backhaul - Hashfi Adha Fadhillah; Ichwan Nul Ichsan (Sistemasi: Jurnal Sistem Informasi, 2026)
This study aims to implement and evaluate the performance of a point-to-point wireless backhaul network between two buildings using the TP-Link CPE220 based on the IEEE 802.11b/g/n standard in a high-interference environment. The implementation was carried out between two buildings approximately 100 meters apart under line-of-sight (LOS) conditions, where the Internet connection from the office building was distributed to the workshop building through the wireless backhaul and subsequently forwarded via a router and an access point. The network performance was evaluated under four testing scenarios: the wireless backhaul link, the workshop router, the access point under no-load conditions, and the access point under a multi-user environment. Measurements were conducted 15 times during the morning, afternoon, and evening using throughput, delay, jitter, and Received Signal Strength Indicator (RSSI) as the evaluation parameters. The results show that the average download throughput decreased from 95.27 Mbps at the source to 57.13 Mbps across the wireless backhaul and 55.56 Mbps at the unloaded access point. Under the multi-user scenario, where 10 devices simultaneously streamed video content, the average download throughput declined to 11.49 Mbps, while delay and jitter increased to 367.29 ms and 66.69 ms, respectively. The analysis indicates that the performance degradation was primarily caused by reduced signal quality over the backhaul link, interference within the 2.4 GHz frequency band, and increased channel contention under multi-user conditions. Nevertheless, the TP-Link CPE220 was able to provide stable inter-building connectivity for small- to medium-scale network deployments, sustaining throughput exceeding 55 Mbps under normal operating conditions.